The Relationship Between Genetic Variants at Loci 9p21, 6q25.1, and 2q36.3 and the Development of Cardiac Allograft Vasculopathy in Heart Transplant Patients - Dlouha, Dana; Janouskova, Kristyna; Vymetalova, Jevgenija; Novakova, Sarka; Chytilova, Sarka; Lukasova, Marianna; Hubacek, Jaroslav A (Genes, 2025)
BACKGROUND: Cardiac allograft vasculopathy (CAV) is an accelerated form of coronary artery disease (CAD) that is characterized by concentric fibrous intimal hyperplasia along the length of coronary vessels, and is recognized as long-term complication after heart transplantation. The chromosomal loci 9p21, 6q25.1, and 2q36.3, represented by their respective leading variants rs10757274, rs6922269 and rs2943634, have been linked with a history of CAD by genome-wide association studies. We aimed to investigate the associations of genetic variants at the loci 9p21, 6q25.1, and 2q36.3 with CAV as genetic risk factors for early prediction. METHODS: Genomic DNA was extracted from paired aortic samples of 727 heart recipients (average age 50.8 ± 12.2 years; 21.3% women) and corresponding donors (average age 39.7 ± 12.0 years; 26.1% women). The variants within the loci 9p21, 6q25.1, and 2q36.3 were genotyped using PCR-RFLP. RESULTS: The recipients' variants of 9p21 (OR 1.97; 95% CI, 1.21-3.19 for GG vs. +A comparison, p = 0.0056) and 2q36.3 (OR 2.46; 95% CI, 1.12-6.17 for +C vs. AA comparison, p = 0.0186) were associated with higher incidence of CAV during the first year following heart transplantation. No such association was found for donor genotypes. CONCLUSIONS: Our data suggest that variants at the locus 9p21 (rs10757274) and 2q36.3 (rs2943634) are associated with early CAV development.
Keywords: Genetic Predisposition to Disease; lidské chromozomy, pár 2; celogenomová asociační studie; jednonukleotidový polymorfismus; Chromosomes, Human, Pair 2; nemoci koronárních tepen; lidské chromozomy, pár 9; Middle Aged; mužské pohlaví; lidské chromozomy, pár 6; Heart Transplantation; Adult; Coronary Artery Disease; Chromosomes, Human, Pair 6; Allografts; ženské pohlaví; Humans; Chromosomes, Human, Pair 9; lidé středního věku; alografty; dospělí; genetická predispozice k nemoci; Female; Genome-Wide Association Study; transplantace srdce; lidé; Male; Polymorphism, Single Nucleotide